Review Article: Effect of Co-Expression Chaperones on the Expression of Intracellular Recombinant Proteins in Escherichia coli - Diandra Firdiani Utami; Mamlikatu Ilmi Azizah; Sriwidodo Sriwidodo; Ryan Adibagus Haryanto; Riyona Desvy Pratiwi; Iman Permana Maksum (Departemen Kimia, 2023)
Escherichia coli is widely used as a host for expressing recombinant proteins due to its well-studied genetics, fast growth, relatively low production costs, and high rate of protein expression. However, despite the high rate of protein expression, the availability of chaperone proteins was often insufficient, resulting in the formation of inclusion bodies due to errors in protein folding. These inclusion bodies can cause the protein to become inactive, and proper protein folding is crucial for maintaining the structure and function of proteins in living organisms. To overcome this limitation, chaperones have been developed as a strategy to help prevent protein folding errors and increase the recovery of soluble protein. In this review, we summarize several experiments related to co-expressing chaperones to enhance the expression of recombinant proteins in E. coli.